#TITLE_ALTERNATIVE# - M. SABRINA (NIM : 12012057), BENAZIR
Tengo Field is a gas and condensate producing field located at Southern Sumatra first discovered at 1991, the field encompasses anarea of 96,5 km2 and currently in development phase. When managing and developing a hydrocarbon field, it is important to recalculate the hydrocarbon reserve in place with the most recend data or technology to evaluate the field potential. Reservoir reserve is calculated with volumetric method and 3D reservoir modeling.The 3D reservoir model in this study is reservoir interval at Baturaja Formation which deposited at Early Miocene. Data used in this study consists of wireline log from well TB-1, TB-2, TB-3, and TB-4, core and cutting data from 1 well, 3D seismic data in time domain, and AI Inversion cube. These data underwent several processes to obtain the goal of the research: well data analysis and correlation, seismic data interpretation, subsurface structure map generation, and reservoir modeling which consist of 3D structural model, petrophysical model, fluid contact determination, and initial gas in place (IGIP) estimation Results from implemented methods concluded that the reservoir interval of Baturaja Formation is limestone at reefal build-up facies which grew on a basement high. The limestone has vug and moldic porosity which developed because of dissolution on vadose zone. Initial gas in place in reservoir interval is estimated 220 BSCF.